(untitled) (CIPEEX, 2025)
The legal institute of ownership in Brazil, particularly in agrarian activities, is undergoing a crisis, exacerbated by the COVID-19 pandemic and measures such as ADPF nº 828 and Resolution 510 of the National Justice Congress. This study investigates the roots of this crisis and the failure of legal mechanisms intended to guarantee security and effectiveness, which have instead resulted in legal barriers. The research aims to analyze political, social, and ideological factors contributing to this crisis and assess its impact on agrarian activities. The study employs qualitative exploratory and descriptive research methods, including bibliographic reviews, case analyses of possession conflicts in rural areas, and the economic and social consequences for rural producers. Results highlight the conceptual shifts in possession, legislative overreach by the Federal Supreme Court, and the suspension of evictions in rural areas, which have legitimized crimes such as possessory embezzlement and worsened conflicts. The inability of the Judiciary to act decisively has led rural producers to resort to self-justice, escalating armed conflicts. The study concludes that injunctive relief is essential to protect possession rights and reduce conflicts, emphasizing the need for harmonization among constitutional powers to recover from this crisis effectively.